Getting air - Gutman, Dan (Aladdin Paperbacks, 2008)
After foiling a terrorist hijacking aboard their airplane, fourteen-year-old Jimmy, his younger sister, and two skateboarding friends crash-land the plane and try to survive in a forest wilderness until help arrives.